Web Based Multimedia Learning System And School Management Information System - Haghsefat, Mani (2009)
In this paper, the author propose a model for web-based Educational information system along with a virtual live classroom which will attach and adapt with any learning management system beside to improve in-classroom learning and post-classroom web-based review and instruction.